Design and encapsulation of anticancer dual HSP27 and HER2 inhibitor into low density lipoprotein to target ovarian cancer cells - Laila J. Alhadad; Gamaleldin I. Harisa; Fars K. Alanazi (Elsevier, 2020)
Tumor cells overexpress low-density lipoprotein (LDL) receptors (LDL-r). Hence, LDL is proposed as a targeting shuttle of anticancer drugs. Therefore, the objective of this study was to synthesize a dual inhibitor of heat shock protein 27 (HSP27) and human epidermal growth factor receptor 2 (HER2) conjugated with cholesterol and encapsulated into LDL for selective targeting of ovarian cancer cells. In the present study, the anticancer agent and its cholesterol conjugate were successfully prepared and characterized physically for color, shape, and melting point. Moreover, the compounds were chemically characterized for 1H NMR and 13C NMR spectra using FTIR and LCMS/MS. Our results revealed that the prepared anticancer agent and its cholesterol conjugate elicited dual HSP27 and HER2 inhibition, as confirmed using western blotting. The anticancer agent (compound D) entered cells and targeted the HSP27 function, thereby reducing HER2 expression. However, a cholesterol-conjugated anticancer agent (compound F) had high cellular uptake and inhibited the growth of SKOV3 cells after encapsulation into LDL. The obtained results concluded that the design of an LDL-encapsulated cholesterol-conjugated HSP27-HER2 dual inhibitor may be a promising approach to realize specific targeted achieve killing of ovarian cancer. Keywords: Drug delivery, LDL, Cholesterol, Heat shock protein 27, Ovarian cancer